2019
DOI: 10.1186/s12889-019-7190-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of behavioural and socioeconomic factors on the community injury rates of adolescents assessed by the south Korean emergency medical services: an ecological approach

Abstract: Background Aim of this study is to determine if peer group risk behaviors and neighbourhood socioeconomic status (SES) would ecologically affect injury incidence according to place and gender among adolescents (aged 13–15) in South Korea. Methods Three variables from the Korea Youth Risk Behavior Survey (2014) were used to represent peer group risk behaviours; current alcohol consumption (cAlc), the experience of violence or bullying (VicVB), and having undergone educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…With respect to maternal sociodemographic characteristics, our findings are consistent with studies showing that mother's reported higher income and education are associated with lower levels of children's depression, opposition problems and mental health problems (Ahn et al, 2019;Anselmi et al, 2010;Gan & Bilige, 2019;Sijtsema et al, 2014). More highly educated parents may have higher educational expectations for their children, stimulating them through play activities and affective behaviors (Drajea & Carmel, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…With respect to maternal sociodemographic characteristics, our findings are consistent with studies showing that mother's reported higher income and education are associated with lower levels of children's depression, opposition problems and mental health problems (Ahn et al, 2019;Anselmi et al, 2010;Gan & Bilige, 2019;Sijtsema et al, 2014). More highly educated parents may have higher educational expectations for their children, stimulating them through play activities and affective behaviors (Drajea & Carmel, 2014).…”
Section: Discussionsupporting
confidence: 88%